Materiality Matters: Corporate Determinants of Disclosure in Sustainability Reports - Rofiki, Achmad; Makaryanawati, Makaryanawati; Sudarto, Triadi Agung (Fakultas Ekonomi, UIN Maliki Malang, 2025)
This study aims to provide empirical evidence of the impact of financial performance, leverage, and business size on materiality disclosure in sustainability reports by classifying the sample as environmentally sensitive or non-sensitive. This research is a quantitative exploratory study. This study used purposive sampling with a variety of criteria, yielding 66 companies and 264 observational data points. The data was analyzed using multigroup panel regression. The study's findings show that financial success positively affects materiality disclosure in sustainability reports in sensitive businesses but has no effect in non-sensitive companies. Leverage does not affect materiality disclosure in sustainability reports in sensitive organizations; nevertheless, it has a beneficial effect in non-sensitive enterprises. Both sensitive and non-sensitive company sizes have a detrimental impact on materiality disclosure in sustainability reports. With the lack of go public companies that consistently publish sustainability reports, this research has implications for go public companies to consistently publish sustainability reports every year and pay more attention to materiality aspects in making them.